Green and facile synthesis of cube-like γ-AlOOH and its usage for fabricating Mg stabilized Na-β″-Al2O3 powders. Issue 14 (1st October 2020) - Wu, Kaipeng; Liu, Diwei; Duan, Hao; Jin, Xinglian; Yin, Shan; Yao, Weitang
Abstract: In this work, we describe the discovery of synthesizing γ-AlOOH particles via direct reaction of Al(OH)3 and H2 O under a green, facile and cost-effective hydrothermal treatment, in which no addition of other additives is required. The as-synthesized γ-AlOOH is in cube-like morphology with micrometres size, which is subsequently used as a precursor to fabricate Mg stabilized Na-β″-Al2 O3 powder with high β″-Al2 O3 phase content through solid-state reaction. Time-dependent experiments are carried out to investigate the microstructure and phase evolutions of the γ-AlOOH precursor during the hydrothermal treatment process, and the sintering temperature on the β″-Al2 O3 phase content and microstructure of the terminal Na-β″-Al2 O3 powder are also studied. The present approach inspires a new and facile way in the fabrication of γ-AlOOH and Na-β″-Al2 O3 on a large scale.